Kvensk grammatikk - Söderholm, Eira (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
Kvensk grammatikk is a comprehensive presentation of the structure of the Kven language, a Baltic-Finnic minority language in Norway. The grammar has been reviewed and approved by Kvensk språkting, the decision-making body for the school norm of Kven. The book was first published in Kven, and Kvensk grammatikk is a somewhat revised version, translated into Norwegian. The book describes the sound system and orthography in Kven. It contains a detailed syntactic-semantic analysis of adposition usage and of the conjunction and subjunction system in the language, and describes the adverb types found in Kven based on their semantic function. The pronouns system as well is thoroughly described in the grammar. The syntax part is based on an ontological-semantic analysis of the verbs. The basic idea is that the verbs of the same ontological-semantic category have the same valency structure; that is, the actual semantic relationships are reflected in the sentence structure. The result is a description of frequent sentence types in the language, what kind of complements they take, and what case the complements have. The morphology part takes care of nominal and verbal inflection, and all of the inflectional categories are described in detail. Their usage is illustrated with example sentences. All linguistic phenomena treated in this grammar are richly illustrated with examples. For some linguistic phenomena, two or three different dialectal variants may occur. The grammar takes into account this dialectic variation in Kven.